ETIKA MASYARAKAT PANDHALUNGAN DALAM MERAJUT KEBHINEKAAN (AGAMA) - Abdus - Sair (Universitas Negeri Malang, 2019)
Indonesia is a unitary country whose people evolve and live in different tribes, races, religions, cultures and languages. This condition occurs as there is one principle known as Bhinneka Tunggal Ika. This principle, hoever, seems to confront or experience “turbulance” along with teh encreases of regional sentiments and majority and minority disparities. Fot instance, the emergance of intolerant groups has threatened the unity of nation. This problem that should be solved sice the proclamation of Indonesian independence in 1945 emerged due to the fact that the goverment has not touched the local wisdom of the community on how to maintain unity. Therefore, this papes aims at presenting the results or research (a case) with qualitiative methods. The data collection is carried out through field observation and indepth interview (unstructure interview). The results of this study indicate that the “pandhalungan community” in Sumberpakem Village Jember District has a strong social integrity about how to maintain unity. They have a cultural grip called a sangkolan, which is a concept of the ancetral heritage of the community on how to respect and appreciate people of difference religions. Morover, there is also the concept of “ taretan dhibik”, which is a glue or tie among residens. Although they have different religions, they consider others as “taretan dhibik” or they brothers. They also say “ataretan saterrosah” (forever brothers)